Three essays on corporate finance - Hasan, Mostafa Monzur (Curtin University, 2015)
This thesis examines the relationship between organization capital and firm life cycle, and their effect on firm risk and the cost of capital. The results show that firms with higher (lower) organization capital or cost of equity are more likely to be in the introduction (growth) and decline (mature) stages. In addition, firm-specific organization capital increases (decreases) idiosyncratic and total (systematic) risk, while management-specific organization capital increases (decreases) systematic (idiosyncratic and total) risk.